CNTFR Genotype and Sprint/power Performance: Case-control Association and Functional Studies - Miyamoto-Mikami, E.; Fujita, Y.; Murakami, H.; Ito, M.; Miyachi, M.; Kawahara, T.; Fuku, N. (International Journal of Sports Medicine, 2016)
The aim of this study was to investigate whether rs41274853 in the 3′-untranslated region of the ciliary neurotrophic factor receptor gene (CNTFR) is associated with elite sprint/power athletic status and assess its functional significance. A total of 211 Japanese sprint/power track and field athletes (62 international, 72 national, and 77 regional athletes) and 814 Japanese controls were genotyped at rs41274853. Luciferase reporter assay was conducted to investigate whether this C-to-T polymorphism affects binding of microRNA miR-675-5p to this region. The TT genotype was significantly more frequent among international sprint/power athletes (19.4%) than in the controls after Bonferroni correction (7.9%, P=0.036, OR=2.81 [95% CI: 1.43–5.55]). Furthermore, in non-athletic young/middle-aged men (n=132), TT genotype carriers exhibited significantly greater leg extension power (26.6±5.4 vs. 24.0±5.4 W/kg BW, P=0.019) and vertical jump performance (50.1±6.9 vs. 47.9±7.5 cm, P=0.047) than the CC+CT genotype carriers. Reporter assays revealed that the miR-675-5p binds to this polymorphic region within the CNTFR mRNA, irrespective of the rs41274853 allele present. Although the functional significance of the rs41274853 polymorphism remains unclear, the CNTFR is one of the candidate genes contributing to sprint/power performance.
Keywords: ciliary neurotrophic factor receptor; elite sprint/power athletes; single nucleotide polymorphism